Brian's winter - Paulsen, Gary. (New York : Delacorte Press, 1998)
Instead of being rescued from a plane crash, as in the author's book Hatchet, this story portrays what would have happened to Brian had he been forced to survive a winter in the wilderness with only his survival pack and hatchet.
Companion book to: Hatchet and The river.
G12
Keywords: Survival -- Fiction; Winter -- Fiction